Closure Strategies for Turbulent and Transitional Flows - Launder, B. E. (Brian Edward); Sandham, Neil D. (Cambridge University Press, 2002)
Turbulence modelling is a critically important area in any industry dealing with fluid flow, having many implications for computational fluid dynamics (CFD) codes. It also retains a huge interest for applied mathematicians since there are many unsolved problems. This book provides a comprehensive account of the state-of-the-art in predicting turbulent and transitional flows by some of the world's leaders in these fields. It can serve as a graduate-level textbook and, equally, as a reference book for research workers in industry or academia. It is structured in three parts: Physical and Numerical Techniques; Flow Types and Processes; and Future Directions. As the only broad account of the subject, it will prove indispensable for all working in CFD, whether academics interested in turbulent flows, industrial researchers in CFD interested in understanding the models embedded in their software (or seeking more powerful models) or graduate students needing an introduction to this vital area.